Developmental stage‐dependent effects of perceived predation risk on nestling tree swallows ( Tachycineta bicolor ) - Sabrina M. McNew; Conor C. Taff; Cedric Zimmer; Jennifer J. Uehling; Thomas A. Ryan; David Chang van Oordt; Jennifer L. Houtz; Allison S. Injaian; Maren N. Vitousek (Ecology, 2024)
The risk of predation directly affects the physiology, behavior, and fitness of wild birds. Strong social connections with conspecifics could help individuals recover from a stressful experience such as a predation event; however, competitive interactions also have the potential to exacerbate stress. Few studies have investigated the interaction between environmental stressors and the social landscape in wild bird populations. In 2 years of field studies, we experimentally simulated predation attempts on breeding female tree swallows ( Tachicyneta bicolor ). At the same time, we manipulated female breast plumage color, a key social signal. Simulated predation events on tree swallows early in the nestling period reduced young nestlings' mass by approximately 20% and shortened telomere lengths. Ultimately, only 31% of nestlings in the predation group fledged compared with 70% of control nestlings. However, the effects of experimental manipulations were timing dependent: the following year when we swapped the order of the experimental manipulations and simulated predation during incubation, there were no significant effects of predation on nestling condition or fledging success. Contrary to our expectations, manipulation of the social environment did not affect the response of tree swallows to simulated predation. However, manipulating female plumage during the nestling period did reduce nestling skeletal size and mass, although the effects depended on original plumage brightness. Our data demonstrate that transient stressors on female birds can have carry‐over effects on their nestlings if they occur during critical periods in the breeding season.